Morphology variation of single walled carbon nanotubes networks by lithography technology for improvement of field effect transistors - Wang, Yilei (2015)
Single walled carbon nanotubes (SWNTs) are potential candidate of channel material instead of silicon in field effect transistors due to their small diameter, high carrier density and flexibility. Two major obstacles in application of SWNT networks in field effect transistors (FETs) are the existence of metallic SWNTs and contact resistance between tubes. To solve these problems, the stripping of SWNT networks and partial alignment of SWNTs has been developed for increasing on/off ratio and mobility of the FETs. This thesis focuses on the design and fabrication of a series of micron pattern to break the metallic percolation pathway and a new partial alignment method to reduce the tube-tube contact resistance in SWNT networks. We fabricate FETs on SiO2/Si wafers with channel width (W) of 20 µm and 50µm, varying channel lengths (L) of 2 − 50 µm and strip width (W') of 2 − 10 µm.). On the SiO2/Si wafer, when on/off ratio of the FETs is > 104, mobility of the best FETs with stripped SWNTs is 3.7±1.25 cm2/V-s. Furthermore, a partially aligned semiconductive SWNT thin film was deposited on silicon dioxide wafers using a novel parallel solution-based immersion-cum-shake method. Superior FET devices with on/off ratio of ~3.2×104 and mobility of 46.5 cm2/V-s are achieved. They are easy and effective ways to reduce both the short coming of metallic SWNTs and the tube-tube resistance in the networks between the source and drain electrodes.